Maria Skłodowska-Curie. Piękno niezłomnego poświęcenia / Maria Skłodowska-Curie. The Obstinate Self‑sacrifice of a Genius - Dei, Luigi (Libere carte, 2018)
Maria's strength of character, the patience and obstinate self-sacrifice mentioned above, began to emerge. As she confessed in a letter: "I have been through some very hard times and the only thing that alleviates the memory of them is that, in spite of everything, I have come through honestly and with my head held high." More emphatically she also wrote, "First principle: never to let oneself be beaten down by persons or by events." A fragment of the book